Viewing I, Daniel Blake in the English Regions: Towards an Understanding of Realism through Audience Interpretation. Issue 3 (July 2021) - Forrest, David; Merrington, Peter
Abstract : This article examines focus group responses to Ken Loach's I, Daniel Blake (2016). Situated in four English regions (North East, North West, South West and Yorkshire and Humber), the focus groups were structured around a process of film elicitation that gathered a set of plural and richly textured responses to the film. Focusing on the participants' understanding of realism within the film, the article complements existing textual analyses of realism in order to understand better the kinds of interpretive resources that audiences bring to their engagement with films such as I, Daniel Blake . We examine in detail how participants drew on different interpretive resources as a set of personal, emotional and intellectual anchoring points that they used to situate and articulate their readings of the film. These resources ranged from related life experiences and personal memories to emotional responses and political views. In particular, we examine how participants interpreted the film through differing degrees of personal familiarity and empathy with the narrative, characters and places depicted, how the participants dealt with the emotional labours of realism and the feelings evoked through representations of place. Using film elicitation to understand the plurality of interpretations of realism has allowed us to develop a located and multifaceted understanding of the affective dimensions of realist film, and to extend the reach of audience studies to a hitherto under-explored genre.